Anti-fungal active fraction to Candida albicans from methanolic extract of camilen flowers (Matricaria chamomilla,L.) - Yudi Rinanto (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
The flowers of kamilen (Matricaria chamomilla, L.) has been used as antifungal in Indonesian traditional medicines. Previous study showed that the extract of flowers inhibited Candida albicans activity. In order to determine the active fraction, the using bioactive-guided fractionation method was used.The air-dried flowers was extracted from methanol. Methanolic extract was fractionated by using n-hexane, chloroform and ethyl acetate. n-Hexane fraction was separated by vacuum liquid chromatography (VLC) by busing silica gel H 60 with mobile phase n-heksan : ethyl acetate and chloroform : methanol by gradient polarity. VLC results fraction was separated by preparative thin layer chromatography with silica gel GF254 and mobile phase n-hexane : chloroform (1:1). The anti-fungal activities of Candida albicans was done by difuse method.Based on the TLC appearence , nine fractions were obtained (FK 1-9) from VLC, and FK-3 was the most active fraction in inhibiting Candida albicans. The result from preparative TLC of FK-3 was 5 subfractions (FP 1-5) Subfraction FP-3 and FP-5 were most active. that had inhibiting radical zone diameter 18 mm in 3% consentration.Key words : Kamilen ( Matricia chamomila, L), Candida albicans, anti-fungal.